2019
DOI: 10.1097/md.0000000000014326
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival of an elderly female with metastatic colon cancer after treated with capecitabine monotherapy

Abstract: Rationale: Colorectal cancer (CRC) is one of the most common cancers all over the world, and approximately 70% of the newly diagnosed patients are over 65 years old. Due to the aging of society, there will be more and more elderly patients of CRC in the future. Treatment of CRC in elderly patients is much more challenging thanks to multiple factors including disabling comorbidities as well as declines in organs function, especially in advanced or metastatic settings. Patient concern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…In addition, the patient selected the regimen. However, several reports have described patients with mCRC who achieved long-term survival after the resection of distant metastases [2][3][4]. Ottone et al reported long-term survival in a patient after oxaliplatin-based chemotherapy and repeated thermoablation of liver metastases from CRC [5].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the patient selected the regimen. However, several reports have described patients with mCRC who achieved long-term survival after the resection of distant metastases [2][3][4]. Ottone et al reported long-term survival in a patient after oxaliplatin-based chemotherapy and repeated thermoablation of liver metastases from CRC [5].…”
Section: Discussionmentioning
confidence: 99%
“…In 2009, a case report described that the use of metronomic capecitabine as a first line and maintenance treatment for an elderly patient with advanced or metastatic colorectal cancer [ 72 ]. The 82-year-old patient was treated with capecitabine (1250 mg/m 2 ) twice a day for days 1 through 14, every three weeks, for a total of 12 cycles.…”
Section: Metronomic Chemotherapy In Elderly Patients With Different T...mentioning
confidence: 99%
“…After two cycles, hepatic metastases decreased by 20% and vanished entirely after eight cycles. Interestingly, the patient experienced hand-foot syndrome and mild, manageable grade 1 leukopenia during the treatment, but there was no sign of metastasis or recurrence [ 72 ].…”
Section: Metronomic Chemotherapy In Elderly Patients With Different T...mentioning
confidence: 99%